Penerapan Rom Pasif untuk Meningkatkan Kekuatan Otot pada Pasien Stroke Non Hemarogik di Icu - Siska Suhartina; Ika Silvitasari; Waluyo Waluyo (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2024)
Stroke is a brain function disorder that occurs suddenly due to blockage or rupture of brain blood vessels. The problem that often arises in stroke patients is movement disorders, patients experience problems or difficulty when walking because they experience problems with muscle strength and body balance or you could say immobilization. Based on these conditions, non-pharmacological management is needed, namely ROM. to find out the results of the application of passive ROM to increase muscle strength in non-hemorrhagic stroke patients in the ICU X Hospital. Descriptive research using case studies, in this application muscle strength was measured before and after being given Range of Motion passive (ROM). Passive ROM is carried out 2x a day for 5 days. Muscle strength Mr. W from (upper extremity) 4/0 and (lower extremity) 3/0 becomes (upper extremity) 5/2 and (lower extremity) 4/2. Power to Mr. P (upper extremity) 5/3 and (lower extremity) 5/3 become (upper extremity) 5/4 and (lower extremity) 5/4. there was an increase in muscle strength in both respondents after ROM was carried out